Challenges and Obstacles in Using Artificial Intelligence Applications and Their Role in Learning Effectiveness among Postgraduate Students - Al-Salhi, Assoc. Prof. Dr. Hanan Khalid Ibrahim Al-Salhi (Sulaimani Journal for Humanities, 2026)
The current study aims to identify the challenges and obstacles associated with the use of artificial intelligence (AI) applications among postgraduate students, and their impact on the effectiveness of the educational process. The study adopted a descriptive research methodology. The research sample consisted of 200 postgraduate students from the College of Education for Humanities at the University of Anbar. A researcher-designed scale was used for data collection after confirming its validity and reliability. The study revealed that there are several challenges and obstacles to using AI applications from the students’ perspectives. These include material and technical barriers, as well as insufficient training and preparation for both students and faculty members.
Keywords: Artificial Intelligence; Educational Effectiveness; Postgraduate Students; Educational Technology; Learning Challenges